Perlindungan Hukum Perlindungan Hukum Pemegang Polis Asuransi Jiwa di Indonesia (Studi Kasus PT. Asuransi Jiwa Raya) - Palyama, Stefany (Magister Ilmu Hukum - Universitas Hang Tuah, 2022)
In 2018, PT. Asuransi Jiwasraya(Persero) experienced a minus and liquidity difficulties which resulted in delays in payment of insurance policy claims from policyholders that were due at the end of 2019 with a value of Rp. 12.4 trillion. The company's assets are recorded at Rp 23.26 trillion, but its liabilities reach Rp 50.5 trillion. The research method is normative juridical by statute approach and conceptual approach aiming to analyze the Legal Protection of the Policy Holders of PT. Asuransi Jiwasraya (Persero) and Comparison of Legal Protection for Policyholders in Singapore. The result of the research is that the legal protection for policyholders (case study of PT. Jiwasraya) is carried out preventively by making regulations on the Policy Guarantee Agency, and repressively through law enforcement, both criminal and civil. The Singapore of Deposit Insurance Company (SDIC) is a guarantee company designated by the Minister as the deposit insurance agency and the policy owner's protection fund. Through the PPF scheme, the Singapore government provides guarantees of protection and legal certainty for policy owners. Therefore, it is important to immediately establish a Policy Guarantee Institution in Indonesia.